The Discourse of Procedural Criminal Law on Follow the Money Concept in Indonesian Anti-Money Laundering Act - Annas Firdaus; Ridwan Arifin (IJCLS (Indonesian Journal of Criminal Law Studies), 2021)
Money laundering is an act attempts to conceal or disguise the origin of money/funds or wealth proceeds of crime through a variety of financial transactions in order to money or possessions that looked as if it came from a legitimate activity or legal. The term money laundering has been known since 1930 in the United States when the mafia buys a legitimate company and officially as one of its strategies.Â These illicit funds not only could damage the market, but also detriment the market, and always do not contribute towards the long-term economic development and stability of the markets where the fund is hidden. Problems of money laundering in English known as money laundering. Money laundering in Indonesia today has developed so alarmingly and requires serious treatment by law enforcement officials at both the police and the institutions established by the Anti Money Laundering Act, namely Transaction Reports and Analysis Center (INTRAC). This paper is intended to analyze the discourse of procedural criminal law on the following the money concept in the money laundering tracking process. This paper confirmed that some different interpretation and limitation has become one of the problems on money laundering tracking process. Especially on follow the money scheme in procedural criminal law. Moreover, it is also emphasized that some judgments have not enough power because of unclear determination in counting the amount of money laundering and counting the losses.